Championing academic integrity in academic development - Cliplef, Lynn; McInnes, Valerie; Munn, Caitlin; Rexe, Scout (Canadian Perspectives on Academic Integrity, 2021)
<span class="NormalTextRun SCXW125114331 BCX9" data-ccp-charstyle="normaltextrun" data-ccp-charstyle-defn="{"ObjectId":"c75fbb6f-2c91-4cf4-b41c-b9ef08ae14dd|55","ClassId":1073872969,"Properties":[134233614,"true",201340122,"1",469775450,"normaltextrun",469778129,"normaltextrun",469778324,"Default Paragraph Font"]}">Curtis et al. (2021) propose that educators with practical, theoretical, and research experience in academic integrity (AI) are well-suited to deliver workshops on the subject. These workshops promote shared understandings amongst attendees, and provide a platform to discuss concerns, devise solutions, and relieve anxieties. Finally, these workshops are most effective when they are a part of themed academic development activities. Assiniboine Community College’s (ACC) Centre for Learning and Innovation (CLI) supports program development and renewal, course and instructional design, teaching strategies, Moodle (Learning Management System), and educational technology. Working with the College’s Academic Integrity and Copyright Officer, CLI has contextualized academic integrity within existing academic development activities, such as a workshops, job aids, and one-on-one sessions. This situates academic integrity as central to our work, rather than an add-on topic. Join ACC’s Centre for Learning and Innovation team members for an overview of where and how we have embedded academic integrity into our offerings, work, and quality standards. Participants will leave this session with practical examples of how teaching and learning centres can be champions for academic integrity.<span class="NormalTextRun SCXW125114331 BCX9" data-ccp-charstyle="eop" data-ccp-charstyle-defn="{"ObjectId":"c75fbb6f-2c91-4cf4-b41c-b9ef08ae14dd|56","ClassId":1073872969,"Properties":[134233614,"true",201340122,"1",469775450,"eop",469778129,"eop",469778324,"Default Paragraph Font"]}">